G233(P) Catheter related blood stream infections among children on hemodialysis: a single center experience. (May 2019) - Kumar, G; Ayyash, B; Tawfik, E; AlMasri, O; AlIsmaili, Z; Hamoudeh, M; AlKhasawneh, E
Abstract : The present study was done at a tertiary care center to study the catheter related blood stream infections (CRBSI) over past seven years and outcomes following these infections. Data on the demographic characteristics, diagnosis and duration on hemodialysis, catheter type, and blood culture results were recorded. All the children had been on tunneled cuffed central vein catheters (TCC). A total of 39 children were included in the study, majority being males (21/39). Median age was 9.2 years. Commonest etiology leading to ESRD was renal dysplasia followed by congenital anomalies of urinary tract. The average number of CVC days was 521 days. The CVC infection rate was 2.37/1000 catheter days. Most common pathogen isolated was Staphylococcus aureus followed by Staphylococcus epidermidis and B cepacia. There had been an outbreak of B cepacia due to multi use aseptic solution Chlorhexidine. None of child died of sepsis. Number of CVC changed due to infection was 27. Infections are significant cause of morbidity among children with CVC on hemodialysis. The infection rate of CVC among children in UAE can be lowered by strict aseptic precautions. Training staff and avoiding use of multi dose antiseptic during hemodialysis procedure may prevent outbreak of infections.